A study of service quality in SOCSO Bintulu / Samsiah Mohammad - Mohammad, Samsiah (2007)
As competition becomes more intense and environmental factors become more hostile, the concern for service quality grows. If service quality is to become the cornerstone of marketing strategy, the marketer must have the means to measure it. The most popular measure of service quality is SERVQUAL, an instrument developed by Parasuraman. This study uses the ‘SERVQUAL’ technique to measure the ten dimensions of service quality which include tangibles, reliability, responsiveness, competence, courtesy, credibility, security, accessibility, communication and understanding consumer. This paper begins by explaining the service quality in the public sector in Malaysia and why service quality is getting more important. The SERVQUAL model has been used in a number of public service environments to assess quality of service provision in terms of what consumers expect and what they actually receive. The main purpose of this study is to gauge the level of service quality in SOCSO Bintulu. Respondents evaluated the service quality in SOCSO Bintulu and SERVQUAL is used to measure on the various service quality dimensions. This study identifies the rank of importance on each service quality determinants. Further, the relationships between the background of respondents and dimensions are examined. Based on the findings, this study shows that courtesy is the most important determinants among all the other dimensions. From this study, it aims to obtain a better understanding of the service quality in SOCSO Bintulu and makes a number of suggestions to improve the service of SOCSO Bintulu in future.